A comparative evaluation of dexmedetomidine and fentanyl to attenuate hemodynamic response to laryngoscopy and intubation - Ozair, Erum; Ali, Qazi Ehsan; Siddiqi, Md Masood Husain; Amir, Syed Hussain; Naaz, Shagufta (Asian Journal of Medical Sciences, 2018)
Background: Laryngoscopy and intubation are associated with a sympathetically mediated circulatory response due to irritation of respiratory tract which is associated with increase in pulse rate and blood pressure that may be dangerous. Aims and Objectives: The aim of the present study was to determine and compare the efficacy of dexmedetomidine and fentanyl in attenuating the hemodynamic response to laryngoscopy and intubation and to detect any complication or side effect as a result of these drugs. Materials and Methods: Following approval by ethical committee, 60 ASA grade I and II patients of either sex undergoing general anaesthesia for elective surgery were included in this study. Patients were randomly divided into two groups of 30 patients each. Dexmedetomidine in a dose of 1μg/kg was given to Group A patients and Fentanyl 2 μg/kg was given to Group B patients. Both the drugs were diluted with normal saline solution to make 10ml and were administered slow intravenous 10 min before induction.The hemodynamic parameters were recorded, demographic data was analyzed using unpaired t-test and hemodynamic variables were analyzed by using unpaired and paired t-test. Side effects were analyzed using chi square test. Result: The two groups were comparable in their demographic profiles. Dexmedetomidine proved itself to be an excellent drug when given intravenously as a premedicant in dose of 1μg/kg to attenuate hemodynamic response to laryngoscopy and intubation. It blunted the hemodynamic response to laryngoscopy and intubation to a greater magnitude than fentanylin a dose of 2μg/kg intravenously as a premedicant. Conclusion: We conclude that fentanyl 2μg/kg i.v. given ten minutes prior to airway instrumentation shows an inconsistent response to laryngoscopy and intubation. Between the two drugs under study, the use of dexmedetomidine 1μg/kg i.v. is satisfactory and produces a more favorable hemodynamic profile while fentanyl 2μg/kg is found to be non- dependable and less effective for the attenuation of the pressor response to laryngoscopy and endotracheal intubation. However, further larger studies are required to strengthen these conclusions. Asian Journal of Medical Sciences Vol.9(1) 2018 65-72